2008
DOI: 10.1111/j.1365-2141.2008.07401.x
|View full text |Cite
|
Sign up to set email alerts
|

Timely diagnosis and management of heparin‐induced thrombocytopenia in a frequent request, low incidence single centre using clinical 4T’s score and particle gel immunoassay

Abstract: SummaryClinicians must promptly decide which patients suspected of having heparininduced thrombocytopenia (HIT) warrant a change in anticoagulation. This single-centre series of 246 HIT testing referrals assessed the combination of clinical score (thrombocytopenia, timing, thrombosis, other causes of thrombocytopenia not evident; 4T's), Diamed ID-Heparin-PF4 immunoassay (PaGIA) and 14C Serotonin Release Assay (SRA) to develop a practical and safe diagnostic strategy for HIT. A total of 142/256 (58%) referrals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
71
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 9 publications
11
71
2
Order By: Relevance
“…30 The positive predictive value of the 4Ts score was as low as 15.4%, a value less than the previously reported range from 21.4% to 100%. [8][9][10]15,[22][23][24][25][26] The false-positive rate of the 4Ts score (percentage of "4T high score" patients in the non-HIT patients) was 11.8%, a value comparable to those previously reported (0-15.3%). [8][9][10]15,[22][23][24][25][26] In contrast, the false-negative rate of the 4Ts scores (percentage of "4T low score" patients in HIT patients) was 54.5% (6/11), a value considerably higher than those previously reported (0-25%).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…30 The positive predictive value of the 4Ts score was as low as 15.4%, a value less than the previously reported range from 21.4% to 100%. [8][9][10]15,[22][23][24][25][26] The false-positive rate of the 4Ts score (percentage of "4T high score" patients in the non-HIT patients) was 11.8%, a value comparable to those previously reported (0-15.3%). [8][9][10]15,[22][23][24][25][26] In contrast, the false-negative rate of the 4Ts scores (percentage of "4T low score" patients in HIT patients) was 54.5% (6/11), a value considerably higher than those previously reported (0-25%).…”
Section: Discussionsupporting
confidence: 78%
“…[8][9][10]15,[22][23][24][25][26] The false-positive rate of the 4Ts score (percentage of "4T high score" patients in the non-HIT patients) was 11.8%, a value comparable to those previously reported (0-15.3%). [8][9][10]15,[22][23][24][25][26] In contrast, the false-negative rate of the 4Ts scores (percentage of "4T low score" patients in HIT patients) was 54.5% (6/11), a value considerably higher than those previously reported (0-25%). [8][9][10]15,[22][23][24][25][26] These findings suggested that many individuals might develop HIT even with a low 4Ts score.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Only studies evaluating a clinical score and/or an IA with HIT diagnosis based on SRA as the gold standard were considered. The sensitivity and specificity (95% CI) of the Ô4 TsÕ probability score and the IA were then reassessed by incorporating the diagnostic performance of SRA reported by Cuker et al [4]; referred to as revisited sensitivity and specificity.Five studies evaluating a clinical score (4 Ts) [6-10] and three studies evaluating an IA were included [6,8,10]. In all of these studies but one [9], HIT was diagnosed if serotonin release was > 20% with 0.1 U mL )1 heparin and < 20%…”
mentioning
confidence: 99%
“…Five studies evaluating a clinical score (4 Ts) [6-10] and three studies evaluating an IA were included [6,8,10]. In all of these studies but one [9], HIT was diagnosed if serotonin release was > 20% with 0.1 U mL )1 heparin and < 20%…”
mentioning
confidence: 99%